1976
DOI: 10.1111/j.1476-5381.1976.tb07663.x
|View full text |Cite
|
Sign up to set email alerts
|

On the Actions of Compounds Related to Dopamine at a Neurosecretory Synapse

Abstract: Royal (Dick) School of Veterinary Studies, Summerhall, Edinburgh EH9 1 QH I The effects of a number of substances related to dopamine, including all its methylated derivatives, were investigated on the membrane potential and response to nerve stimulation of cockroach salivary gland cells. 2 Only N-methyldopamine (epinine), N,N-dimethyldopamine and N,N-dimethylnoradrenaline, all with unsubstituted hydroxyl groups, directly resembled dopamine in producing a hyperpolarization which could be as large as that cause… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1976
1976
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…IoA). IoB), in the absence of nerve stimulation (Ginsborg, House & Turnbull, 19763;Bowser-Riley & House, 1976). IoB), in the absence of nerve stimulation (Ginsborg, House & Turnbull, 19763;Bowser-Riley & House, 1976).…”
Section: (B) Resting Potential Of Mnar Cellsmentioning
confidence: 99%
“…IoA). IoB), in the absence of nerve stimulation (Ginsborg, House & Turnbull, 19763;Bowser-Riley & House, 1976). IoB), in the absence of nerve stimulation (Ginsborg, House & Turnbull, 19763;Bowser-Riley & House, 1976).…”
Section: (B) Resting Potential Of Mnar Cellsmentioning
confidence: 99%
“…3B) and by 5-hydroxytryptamine (cf. Ginsborg, House & Turnbull, 1976;Silinsky, 1974). It is tempting to suppose that the effects are due to liberation of the transmitter, although evidently more direct experiments will be required to rule out the possibility of a post-synaptic origin (cf.…”
Section: Indirectly Acting Agonistsmentioning
confidence: 99%
“…A structure-activity study has shown that the two catechol OH groups are necessary but not sufficient for agonist action, because N-acetyldopamine is inactive (Ginsborg et al, 1976b).…”
Section: +mentioning
confidence: 99%